Effectiveness and reporting standards of psychological interventions for improving short-term and long-term pain outcomes after total knee replacement: a systematic review - Rachael Gooberman-Hill; Vikki Wylde; Katie Whale; Andrew Beswick; James Rathbone; Kavita Vedhara (BMJ Open)
Objectives To assess the effectiveness and reporting standards of psychological interventions for improving outcomes after total knee replacement (TKR).Design Medline, Embase, and PsycINFO were searched from inception to up to 9 May 2019 with no language restrictions applied. Randomised controlled trials (RCTs) assessing the effectiveness of psychological interventions for short-term and long-term postoperative pain after TKR were included. Screening, data extraction, and assessment of methodological quality were performed in duplicate by two reviewers. The primary effectiveness outcome was postoperative pain severity and the primary harm outcome was serious adverse events. Secondary outcomes included function, quality of life, and psychological well-being. Reporting standards were assessed using the Template for Intervention Description and Replication (TIDieR) checklist for intervention reporting.Results 12 RCTs were included, with a total of 1299 participants. Psychological interventions comprised music therapy (five studies), guided imagery and music (one study), hypnosis (one study), progressive muscle relaxation with biofeedback (one study), pain coping skills programme (one study), cognitive–behavioural therapy (two studies), and a postoperative management programme (one study). Due to the high heterogeneity of interventions and poor reporting of harms data, it was not possible to make any definitive statements about the overall effectiveness or safety of psychology interventions for pain outcomes after TKR.Conclusion Further evidence about the effectiveness of psychological interventions for improving pain outcomes after TKR is needed. The reporting of harm outcomes and intervention fidelity is currently poor and could be improved. Future work exploring the impact of intervention timing on effectiveness and whether different psychological approaches are needed to address acute postoperative pain and chronic postoperative pain would be of benefit.PROSPERO registration number CRD42018095100.